Treatment needs and diagnosis awareness in primary care patients with chronic kidney disease - McIntyre, Natasha J (Royal College of General Practitioners, 2012)
BACKGROUND: GPs in England are required to keep a register of patients with chronic kidney disease (CKD). National Institute for Health and Clinical Excellence (NICE) guidelines recommend regular follow-up, but patients are perceived to be low risk and not requiring active management. AIM: To assess treatment needs of CKD stage 3 patients in primary care, as well as their awareness of CKD. DESIGN AND SETTING: A cross-sectional analysis from a longitudinal prospective study in 32 general practices. METHOD: A total of 1741 participants underwent clinical assessment including urine and blood tests. Participants were asked about awareness of their CKD. Results were reviewed and a letter recommending treatment in line with NICE guidelines was sent to their GP. RESULTS: The mean age of participants was 73 ± 9 years; 60% (n = 1052) were female and diabetes was present in 17%; 67% of participants required further intervention. Most required improved control of hypertension (n = 1576; 33.1% of cohort). Other recommendations included advice to investigate anaemia (n = 1142; 8.2%) or stop nephrotoxic drugs (n = 1120; 7.5%). Less than 6% of participants met NICE criteria for referral to nephrology services and 41% were unaware of their CKD diagnosis. Multivariable analysis identified subjects with formal educational qualifications, age <75 years, estimated glomerular filtration rate (eGFR) 30–44 ml/min/1.73 m(2), and significant albuminuria as more likely to be aware of their diagnosis. CONCLUSION: The study data show that the majority of patients required at least one intervention to improve the management of their CKD. Most interventions could be delivered in primary care and only a minority required nephrology referral. Many patients were unaware of their CKD diagnosis, and efforts should be made to improve this to facilitate involvement in their care.